Language and automata theory and applications 5th International Conference, LATA 2011, Tarragona, Spain, May 26-31, 2011. Proceedings - LATA (Conference) 2011 Tarragona, Spain); Dediu, Adrian-Horia.; Inenaga, Shunsuke; Martín-Vide, Carlos; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 5th International Conference on Language and Automata Theory and Applications, LATA 2011, held in Tarragona, Spain in May 2011. The 36 revised full papers presented together with four invited articles were carefully selected from 91 submissions. Among the topics covered are algebraic language theory, automata and logic, systems analysis, systems verifications, computational complexity, decidability, unification, graph transformations, language-based cryptography, and applications in data mining, computational learning, and pattern recognition.
Electronic reproduction.
Keywords: Machine theory -- Congresses; Formal languages -- Congresses; Mathematical linguistics -- Congresses; Electronic books